Intensive aquaculture and sustainable regional development in the Arctic region – from controversy to dialogue (AquaLog) - Hersoug, Bjørn; Karlsen, Kine Mari; Solås, Ann-Magnhild; Kvalvik, Ingrid; Johnsen, Jahn Petter; Young, Nathan; Brattland, Camilla; Schreiber, Dorothee; Simonsen, Knud; Olofsson, Erik; Thorarensen, Helgi (Nofima, 2017)
The main objective of the AquaLog project is to understand factors and forces that influence the aquaculture controversy in the Arctic communities. This report summarizes the second workshop in Vancouver, Canada 23-27th April 2017. The project is funded by the Nordic Council of Minister and the Norwegian Fram Centre. Aqualog er et nettverksprosjekt finansiert av Nordisk Ministerråd og Framsenteret. Hensikten med prosjektet er å øke forståelsen av konflikter rundt akvakultur og hvordan disse håndteres i de arktiske landene. Rapporten oppsummerer prosjektets andre arbeidsseminar, som fant sted i Vancouver, Canada fra 23. -27. april 2017.